2012
DOI: 10.1161/atvbaha.112.248492
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Identifies KNG1 as a Genetic Determinant of Plasma Factor XI Level and Activated Partial Thromboplastin Time

Abstract: Objective-Elevated plasma levels of coagulation factor XI (FXI) are implicated in the pathogenesis of venous thromboembolism and ischemic stroke, and polymorphisms in the F11 gene are associated both with risk of venous thromboembolism and an elevated plasma FXI level. Methods and Results-Here, we report the first hypothesis-free genome-wide genetic analysis of plasma FXI levels.Two genome-wide significant loci were detected in the family-based Genetic Analysis of Idiopathic Thrombophilia 1 cohort: one located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
3
34
1
Order By: Relevance
“…Our results indicate that KNG1 plays a relevant role in the CIP not only at a molecular level, but also at a genetic level. This result is particularly interesting since allelic variants in KNG1 were previously associated with risk of thrombosis [33]. Our result strengthens previous conclusions concerning the association of KNG1 with thrombosis suggesting that KNG1 plays a role in the regulation of CIP, even without the influence of the FXI or the FXII levels, since neither FXI nor FXII levels show a specific weight within this metaphenotype (Fig 1.c).…”
Section: Discussionsupporting
confidence: 87%
“…Our results indicate that KNG1 plays a relevant role in the CIP not only at a molecular level, but also at a genetic level. This result is particularly interesting since allelic variants in KNG1 were previously associated with risk of thrombosis [33]. Our result strengthens previous conclusions concerning the association of KNG1 with thrombosis suggesting that KNG1 plays a role in the regulation of CIP, even without the influence of the FXI or the FXII levels, since neither FXI nor FXII levels show a specific weight within this metaphenotype (Fig 1.c).…”
Section: Discussionsupporting
confidence: 87%
“…Although some of these studies have identified the involvement of common single nucleotide polymorphisms in the structural F11 gene and alterations in other genes that might indirectly regulate plasma levels of this factor [11][13], the molecular mechanisms of FXI regulation are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The genome-wide association studies (GWAS) of plasma FXI levels performed in the GAIT-1 Project showed significant associations with variants in the KNG1 and F11 loci. Those results were replicated in a population-based Swedish cohort [15]. The KNG1 encodes for a high molecular weight kininogen (HMWK).…”
Section: Introductionmentioning
confidence: 81%